Management of Emotions in Accelerated Medical Relationships - Anne Roelsgaard Obling (Copenhagen Business School (CBS), 2012)
This thesis is the result of an ethnographic fieldwork at a major university hospital in Denmark that I undertook between June 2009 and January 2011. I was an `embedded' observer in a cancer clinic and entirely dependent on the staff – administrative and clinical – for access to facilities, people and diseases. That said, I was never asked to modify my writings in any way or to show the content of my field notes or tape recordings. Neither does the hospital have any formal share in the overall thesis. The responsibility for the final outcome is on my shoulders alone. As an embedded observer I was to handle personally sensitive data, such as specific details in patient records, with confidentiality. There is no information in my writings which can be traced – directly or indirectly – back to individual patients or relatives at the hospital and hence disclose their identity. My observations lasted anywhere from 20 minutes (the length of a typical staff meeting) to five working days in a row. During a day of observation, I followed doctors from they arrived in the early mornings; when they attended the morning conferences, until they left the hospital in the late afternoon after hours of clinical work in the outpatient clinic. I also followed them in their offices and in the operation theatres. Many tableaux from the thesis you are reading now were recorded in my notebook and then reconstructed in the later writing. Wherever possible, I have used my free access to the hospital to check the accuracy of my writing, for example by procuring typical situations more than once or by going through precarious details with involved staff members. Statements that appear in quotation marks (`…') were recorded directly on my tape recorder or in my notebook while the person was speaking, or immediately hereafter. Through the process I have shared my ideas with the staff members involved to make sure that they understood the purpose of my work and also in order for them to have a chance to feel comfortable with my presence. Throughout the thesis, I have shortened quotes from documents and interviews in order to make the text more readable. In addition to my fieldwork at the hospital, I have worked with the sociologist Nanna Mik-Meyer. In her work, Mik-Meyer has focused on general practitioners and their preoccupation with patients who attend the consultancy with medically unexplained symptoms. Parts of the raw data material from some of her previous studies became the basis of a co-authored article, which is included in this thesis. Utterances from individuals described in this article are directly quoted from a larger quantity of interviews with general practitioners in primary care medicine.
hdl:10398/8419
Keywords: 650